120 COMPARING THE FUNCTIONAL INDEPENDENCE MEASURE AND THE BARTHEL INDEX FOR ASSESSMENT OF OLDER ADULTS. (25th October 2022) - Alookaran, S; Cannon, E; Williams, D; O'Donnell, M; Harty, E; Shovlin, L; McDonagh, E; Cawley, T; Drumm, B; Kelly, A; Porter, S
Abstract: Background: Measuring and reporting health outcomes have become an essential component to the rehabilitation of older persons that can be often complicated by increasing frailty and medical complexity. The Integrated Care Team for Older Persons (ICTOP) is a multidisciplinary service offering domiciliary based interventions over a 4-6 week period for those aged over 65 years, with a Rockwood Clinical Frailty scale (CFS) of 3-6. The Barthel Index is currently used in the ICTOP Comprehensive Geriatric Assessment (CGA). It is an ordinal scale and measures activities of daily living performance. Functional Independence Measure (FIM) is used to assess and grade a person's functional status. The FIM and Barthel Index are well recognised validated tools. The objective is to measure which outcome is more comprehensive and sensitive for the patient cohort over the 6-week intervention. Methods: Ethical approval was received for the study. The participants were recruited over a 3 month period and met ICTOP inclusion criteria .The sample size was 20.The FIM and Barthel Index scores were documented and recorded on initial CGA, and on discharge. Results: Participants were aged between 72-91 years with a mean age of 82 years, 55 % of participants were moderately frail, 15% mildly frail, 10% vulnerable and 20% managing well as per categorisation using the CFS. On paired t-test the Barthel Index and FIM scores showed similar responses in the cohort. However, the FIM score was more sensitive. These findings suggest that the FIM score had no statistical significance over the Barthel Index in evaluating change in this cohort of patients. Conclusion: This study has provided valuable information which will impact future practice for the ICTOP Team. It afforded an opportunity to monitor the Team's practice and explore the most effective measurement tool for this cohort of participants.